Developing Flash Card 'Flat Facts' Media to Enhance Creative Thinking Skills in Elementary Geometry Learning - Fadhilah, Febri Mayasari Miftakhul; Kusuma, Dani (Journal of Innovation and Research in Primary Education, 2025)
Creative thinking skills are fundamental competencies that must be developed in elementary mathematics education, particularly in geometry learning. However, Indonesian students' creative thinking abilities remain low, as evidenced by international assessments like TIMSS and PISA. This study aimed to develop Flash Card "Flat Facts" media to enhance creative thinking skills among fourth-grade students in flat geometry learning. This research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects were 18 fourth-grade students from SD Negeri Sumberejo 02, Pabelan District, Semarang Regency. Data collection instruments included observation sheets, structured interview guides, creative thinking ability tests measuring fluency, flexibility, originality, and elaboration indicators, and response questionnaires. Data analysis used descriptive quantitative methods with paired sample t-tests and N-Gain calculations to measure effectiveness. Expert validation showed excellent results with 84% for content validity and 98.3% for media design validity. The media demonstrated significant effectiveness in improving students' creative thinking abilities, with a mean N-Gain score of 0.7208 (72.08%) categorized as "high improvement." Statistical analysis revealed significant differences between pretest and posttest scores (p < 0.001). The media also showed exceptional practicality with 89% student satisfaction and 96% teacher approval. Flash Card "Flat Facts" successfully enhanced creative thinking skills in geometry learning through interactive and visual approaches. The dual-coding design combining visual and textual elements effectively facilitated knowledge construction among elementary students. The high user satisfaction indicates successful integration into authentic classroom environments, supporting the implementation of student-centered learning approaches aligned with Indonesia's Kurikulum Merdeka philosophy.